Perancangan User Experience Aplikasi Sistem Informasi Gereja menggunakan Metode Human-Centered Design (Studi Kasus: GPdI Hope Jombang)rmasi Gereja Menggunakan Metode Human-Centered Design (Studi Kasus: GPdI Hope Jombang) - Phillip Tothalove Chrisyuono; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Many essential sectors of life are affected by Covid-19, one of them is religious sector. The Ministry of Religious Affairs issued a Circular Letter of the Minister of Religious Affairs 2022 concerning the Implementation of Worship/Religious Activities. In that circular letter, there are restrictions on the distance and number of congregations present. GPdI Hope Jombang is one of the churches that implements the congregational data collection process. GPdI Hope Jombang requires its congregation to register their self before coming to worship. The registration and attendance process that is carried out manually makes the registration data and attendance of the congregation often lost. In order to help the manager and congregation of GPdI Hope Jombang in carrying out all of the spiritual activities, the author designed the user experience application for church information system using the human-centered design method. For the effectiveness aspect, tested using usability testing and the result is 93% for the manager's display and 91% for the congregation's display. For efficiency aspect, tested using usability testing and the result is 0.163 goals/second for the manager and 0.104 goals/second for the congregation. For user satisfaction aspect, tested using the system usability scale (SUS) and the result is 96 for the manager's display which it's in the Excellent category, and 92 for the congregation's display which it's in the Excellent category. Then for the user experience questionnaire (UEQ), results for the manager's display and the congregation for the aspects of attractiveness, efficiency, dependability, stimulation, and novelty in the excellent category, while perspicuity gets the above average category.